Faktor-Faktor Yang Berhubungan Dengan Preeklampsia Pada Ibu Hamil Trimester III - Ratna Puspitasari; Nirmala Harahap; Eka Bati Widyaningsih (Politeknik Karya Husada, 2025)
The largest AKI is caused by bleeding which is triggered by the incidence of preeclampsia and eclampsia which ranks second among all cases affecting pregnant women. Data from Banten Province shows that 35.6% of pregnant women experience preeclampsia. At Brawijaya Tangerang Hospital from 2022 to 2023 there will be an increase in the incidence of preeclampsia at Brawijaya Tangerang Hospital by 10%. To determine the factors associated with preeclampsia in pregnant women at Brawijaya Tangerang Hospital in 2023. The research method used was quantitative research with a cross sectional study design using secondary data (medical records) with a sample of 87 third trimester pregnant women who experienced preeclampsia at the hospital. Brawijaya Tangerang. There is a relationship between age and preeclampsia in third trimester pregnant women with a p-value of 0.006